Employees’ Perceptions of Perceived External CSR towards Perceived External Prestige - Bista, Sita; Modi, Devendra Kumar (Nepal Journal of Multidisciplinary Research, 2022)
Correction: On 21st September 2022 the co-author was changed from Dr D.K. Maheshwari to Prof. Dr. Devendra Kumar Modi Organizational behavior researchers are currently very interested in employee perception. An organization's activities may have an impact on employee perception. People desire to be treated decently by nature. Every person has the intrinsic ability to treat others with respect. Even if a person observes that another person is not being treated fairly, they may interpret this as a personal attack on themselves. Therefore, according to the OB research, employees may react to unfair treatment not only for themselves but also for stakeholders outside the firm, such as the community, environment, and consumers. Employees begin to feel prestigious and form a favourable attitude toward the company if they perceive it to be acting ethically toward external stakeholders. Thus, this study aimed to find out the relationship between perceived external corporate social responsibility and perceived external prestige. The data were collected from 6 commercial banks of Nepal. There were 381 respondents. The results show that there is significant correlation between external corporate social responsibility and external prestige of companies.